Penerapan Logika Fuzzy untuk Pembentukan Sutradara Otonom dalam hal Pencahayaan pada Machinima - Andreas; Mauridhi H. Purnomo; Mochamad Hariadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Lighting is one of the most important things in the world of cinematography. There are several parameters that must be considered to produce good lighting. There are so many permutations in the lighting arrangement. It causes complexity of the process and there is no simple way to do the calculation. This complexity is compounded by the fact that each director has their own style in lighting arrangements in the film production process. This paper refers to the tabulation of the results of interviews with three movie directors and then the similarities of the three were taken. In this study, a fuzzy logic structure was built with five parameters of lighting arrangement, namely: the situation of the set, the camera's point of view, the installed light intensity, the position and direction of the camera, and the emotions of the character. This research was conducted using 20 animated movie scenes that were built using Unity. The assessment of the output is done manually by several animated film designers. As a result, the designers assess that 80% of the lighting arrangement has been as expected.